Neurofilament light chain in serum of cancer patients with acute neurological complications - Amulya Gottiparthy; Keng Lam; Suprateek Kundu; Zixi Yang; Ivo Tremont-Lukats; Sudhakar Tummala (CNS Oncology)
Aim: Neurofilament light chain (NfL) is a nonspecific sensitive biomarker of axonal damage.Methods: This case series identified cancer patients with neurological complications who had serum NfL measurements and paired these results to outcomes.Results: NfL serum levels were available in 15 patients with hematological malignancies or solid tumors. The neurological complications studied were immune effector cell–associated neurotoxicity syndrome, immune checkpoint inhibitor–related encephalopathy, anoxic brain injury, Guillain-Barre syndrome, hemophagocytic lymphohistiocytosis, transverse myelitis, paraneoplastic syndrome, central nervous system demyelinating disorder and chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids. All patients but one with serum NfL >900 pg/ml died during hospitalization.Conclusion: Serum NfL levels consistently corresponded to death, disease severity or recovery in this series.